ANALISIS TEORITIK KEBERBAKATAN SISWA - Syarifan Nurjan (AL-ASASIYYA: Journal Of Basic Education, 2018)
This analysis aims to develop students' giftedness, which the term gifted is described by Plato as Men of gold or "golden man," a person of superior intellectual character, then translated from the English word gifted, the other being giftedness, gifted, talented, creative, insightful, genius and precocious. So that the meaning of gifted people who have a high level of intelligence, judging from the scores obtained from intelligence tests. Two approaches to viewing giftedness, which is one-dimensional and multidimensional, namely the dimensions of intelligence and various other dimensions. And gifted models are (a) genetically oriented, (b) cognitive models, (c) achievement-oriented, and (d) systemic models. The development of students' giftedness is someone from the chronological age range in the 12-18 year age range, and is undergoing psychosocial changes related to identity, independence, friendship, sexuality and achievement, and has general or intelligence abilities above average, high creativity, and commitment to the task.